IMPLEMENTASI PROSES DAN UPAYA OPTIMALISASI PEMUNGUTAN PAJAK AIR TANAH UNTUK PENINGKATAN PAD DI BKAD KABUPATEN SLEMAN - Salsabila, Syifa; Kartika, Fiki; Septianingsih, Cesilia Arum; Ramadhan, Rahmad Puji Nur; Zuhri, Saifudin (LP2M STP Mataram, 2024)
This service activity aims to find out: (1) Implementation of the Ground Water Tax Collection Process in the Sleman Regency BKAD, (2) Efforts to Optimize Ground Water Tax Collection to Increase Regional Original Income in the Sleman Regency BKAD, (3) Obstacles Faced by the Sleman Dalam Regency BKAD Implementation of the Ground Water Tax Collection Process and solutions to overcome these obstacles. The methods used in collecting data and answering problems are observation, interviews, documentation studies and literature studies. The results of the internship activities show that: (1) The implementation of the Ground Water Tax Collection Process at BKAD Sleman Regency has been implemented properly and correctly in accordance with the regulations and main tasks and functions. (2) Efforts to Optimize Ground Water Tax Collection to Increase Original Regional Income are carried out by BKAD Sleman Regency through reconciliation activities, additional workforce, data collection, socialization and collection through STPD. (3) The obstacles faced by the Sleman Regency BKAD in implementing the Ground Water Tax collection process are the delivery of SKPD that is not on target, an untrustworthy attitude, social recognition, lack of public knowledge about Ground Water Tax, lack of budget for paying Ground Water Tax, and late delivery . NPAT data by the Province